The Cupak Community's Ethnoscience in Utilizing Banana Pangek as a Biology Learning Resource - Rahmi Ramadhani; Zulyusri Zulyusri; Fitri Arsih (Bioeducation Journal, 2026)
Local wisdom represents a form of knowledge that develops within communities and is transmitted across generations, reflecting a close relationship between culture and science. One example of local wisdom in Minangkabau society is the tradition of serving food in small cups (cawan) during funeral ceremonies in Nagari Cupak, Gunung Talang District, Solok Regency. The cawan typically contains rice, pangek pisang (banana cooked in coconut milk and spices), and chili paste. This study aims to examine the ethnoscience values embedded in this tradition based on interviews with a local traditional cook. This research employs a qualitative approach using in-depth interviews and literature study. The findings reveal that the preparation and serving of pangek pisang involve various scientific concepts, including biological aspects such as nutritional content and food digestibility, chemical processes such as starch gelatinization and emulsion formation in coconut milk, and physical principles such as heat transfer during cooking. In addition, the tradition reflects strong social values, including mutual cooperation, respect for guests, and cultural continuity.